Hadamard-Type k-Fractional Integral Inequalities for Exponentially α, h−m-Convex Functions. (24th October 2020) - Jung, Chahn Yong; Farid, Ghulam; Bibi, Sidra; Nisar, Kottakkaran Sooppy; Kang, Shin Min
Abstract : The class of exponentially α, h − m -convex functions has been discovered to unify different kinds of convexities. This paper finds new Riemann–Liouville fractional Hadamard-type inequalities for this generalized class of convex functions. These results further have their consequences which are presented in the form of corollaries. Moreover, some known results are identified in the form of remarks.